Old age ang longevity in daily life of education: tracing (im)impossibilities (im)possibilities in curriculum (micro)policies (PerCursos, 2023)
This paper has as objective reflect about old age, aging and longevity in the field of education. Among the issues raised, we seek to reflect on the following questions: is this theme present at school or on curriculum? What is the expectation related to the teaching environments when elaborating the meanings of old age and a certain perspective to defend the longevity? Therefore, we are interested in looking at how the schooling processes mobilize the production, marking, and regulation of generational difference and longevity. The problematizations of the work are based on post-critical theoretical and methodological precepts, using a methodology that strives in the descriptions, analysis and problematization about discursive artifacts. Specifically, the discourses present in the BNCC (National Common Curriculum Base) and the statute of the elderly person, considering that are produced in a way that engenders domains and power relations, giving support to certain games of truth, being associated with official documents and public policies related to the elderly that are articulated in/with the daily life of basic education schools. It was possible to analyze how the debate about old age and aging begins as a "package" in the public curriculum policy - the BNCC - which is presented as the main curricular proposal for Brazilian schools. In addition, we sought to problematize and expand the type of approach that schools can undertake to address the issues of aging, old age and longevity in a complex and pluralistic way when they propose to reflect on such relevant themes.
Keywords: BNCC; old age; basic education